Validation of the name Mitreola crystallina (Loganiaceae), a new species endemic to southwestern China - You, Jian-Rong; Ran, Juan; Liu, Cheng; Shui, Yu-Min; Li, Jia-Xiang; Wu, Lei (Phytotaxa, 2020)
Mitreola crystallina was proposed in 2006, but not valid. Here, we validate the name by giving a complete description, diagnosis, and illustration as a new species of Loganiaceae. Morphologically, it is most similar to M. pedicellata, but can be distinguished by its stems erect (vs. creeping), corolla lobes blue (vs. white), and stamens inserted at or near base of the corolla tube (vs. middle to nearly mouth of corolla tube). It is endemic to the shady cliffs of limestone forests of Malipo County, southwest China. The conservation status was assessed as data deficient (DD) according to the IUCN Red List categories and criteria. And a key to species of Mitreola in China is provided.